Dorsolateral prefrontal transcranial magnetic stimulation in patients with major depression locally affects alpha power of REM sleep - Pellicciari, Maria C.; Cordone, Susanna; Marzano, Cristina; Bignotti, Stefano; Gazzoli, Anna; Miniussi, Carlo; De Gennaro, Luigi (Frontiers in Human Neuroscience, 2013)
Sleep alterations are among the most important disabling manifestation symptoms of Major Depression Disorder (MDD). A critical role of sleep importance is also underlined by the fact that its adjustment has been proposed as an objective marker of clinical remission in MDD. Repetitive transcranial magnetic stimulation (rTMS) represents a relatively novel therapeutic tool for the treatment of drug-resistant depression. Nevertheless besides clinical evaluation of the mood improvement after rTMS, we have no clear understanding of what are the neurophysiological correlates of such treatment. One possible marker underlying the clinical outcome of rTMS in MDD could be cortical changes on wakefulness and sleep activity. The aim of this open-label study was to evaluate the efficacy of a sequential bilateral rTMS treatment over the dorsolateral prefrontal cortex (DLPFC) to improve the mood in MDD patients, and to determine if rTMS can induce changes on the sleep structure, and if those changes can be used as a surrogate marker of the clinical state of the patient. Ten drug-resistant depressed patients participated to ten daily sessions of sequential bilateral rTMS with a low-frequency TMS (1 Hz) over right-DLPFC and a subsequent high-frequency (10 Hz) TMS over left-DLPFC. The clinical and neurophysiological effects induced by rTMS were evaluated respectively by means of the Hamilton Depression Rating Scale (HDRS), and by comparing the sleep pattern modulations and the spatial changes of EEG frequency bands during both NREM and REM sleep, before and after the real rTMS treatment. The sequential bilateral rTMS treatment over the DLPFC induced topographical-specific decrease of the alpha activity during REM sleep over left-DLPFC, which is significantly associated to the clinical outcome. In line with the notion of a left frontal hypoactivation in MDD patients, the observed local decrease of alpha activity after rTMS treatment during the REM sleep suggests that alpha frequency.